NEGATIVE THOUGHTS AND SELF-CONFIDENCE AMONG ATHLETES WITH DIFFERENT SPORTS EXPERIENCES: A META-ANALYSIS - José Vasconcelos-Raposo; João Palumbo; Ana Carvalho; Joana Borges; Carla M. Teixeira (PsychTech & Health Journal)
An athlete’s sporting experience is a factor associated with better-coping strategies and emotional regulation, especially concerning competitive anxiety and its symptoms. To verify whether more experienced athletes have lower rates of negativism and higher levels of self-confidence, we compared the means of these two variables between athletes with more and less experience. A meta-analysis was performed, following the PRISMA model. Seven articles were selected that measured, through the Competitive State Anxiety Inventory – 2 (CSAI-2 or its shortened version, CSAI-2R), the levels of self-confidence and negativism of high-performance athletes with different sports experiences. Significant statistical differences were found regarding the levels of negativism between athletes with more and less experience (p < .001). The same occurred with the levels of self-confidence between athletes with more and less sports experience (< .001). The results align with our initial hypothesis, formulated by Martens et al. (1990), that athletes with more experience would have higher self-confidence and lower negativism averages. One of the reasons may be using more effective coping strategies that are improved during the career years.